2009
DOI: 10.1099/mic.0.023143-0
|View full text |Cite
|
Sign up to set email alerts
|

The conserved portion of the putative virulence region contributes to virulence of avian pathogenic Escherichia coli

Abstract: Colibacillosis is a common systemic disease of worldwide economic importance in poultry, caused by Escherichia coli. E. coli are normally found in the intestines of poultry, but some strains are able to cause extraintestinal disease. Plasmid pVM01 is essential for virulence in avian pathogenic Escherichia coli (APEC) strain E3 in chickens after aerosol exposure and contains the virulence-associated genes iucA, iss and tsh in distinct regions. The determination of the complete sequence of this plasmid identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…6). To date, four ColBM plasmids have been sequenced, including three from APEC strains (pAPEC-O1-ColBM, pVM01, and pAPEC-O103-ColBM) (Table 3) (87,181) and one from an MDR E. coli strain isolated from a coastal environment (pSMS35_130) ( linkage of MDR-encoding regions with the ColV-encoded PAI is particularly disturbing, since it provides a means for the selection of highly virulent strains through the use of antibiotics. pCVM29188_146 harbors typical ColV-associated virulence genes but also contains Tn10 downstream of the F transfer region, an atypical region for accessory components (Fig.…”
Section: Colv and Colbm Plasmidsmentioning
confidence: 99%
“…6). To date, four ColBM plasmids have been sequenced, including three from APEC strains (pAPEC-O1-ColBM, pVM01, and pAPEC-O103-ColBM) (Table 3) (87,181) and one from an MDR E. coli strain isolated from a coastal environment (pSMS35_130) ( linkage of MDR-encoding regions with the ColV-encoded PAI is particularly disturbing, since it provides a means for the selection of highly virulent strains through the use of antibiotics. pCVM29188_146 harbors typical ColV-associated virulence genes but also contains Tn10 downstream of the F transfer region, an atypical region for accessory components (Fig.…”
Section: Colv and Colbm Plasmidsmentioning
confidence: 99%
“…80-kb region enriched in virulence-associated loci, including four iron acquisition systems (iutA, iucABCD, sitABCD, iroBCDN), tsh, iss, and other candidate virulence genes (44). This region also appears to contribute to air sac colonization and the induction of pathology by an O nontypeable:H28 APEC field isolate in poultry (45). Of the other plasmids found in 7122, pChi7122-2 is an IncFII plasmid that encodes an ABC iron transport system (eitABCD), whereas pChi7122-3 (IncI2) carries a putative type IV fimbrial locus (43).…”
mentioning
confidence: 99%
“…Carraminana et al [6] reported that 40% of the antibiotics produced in the United States were used in stock feeds. The widespread use of various antibiotics for treating animal infections has created antibiotic resistant bacterial strains [7] [8]. Antimicrobial resistance is one of our most serious health threats.…”
Section: Introductionmentioning
confidence: 99%